What Drives the Continental Crust To Be Extremely Hot So Quickly?. Issue 11 (29th November 2019) - Huang, Guangyu; Guo, Jinghui; Jiao, Shujuan; Palin, Richard
Abstract: The widespread spatio‐temporal occurrence of ultrahigh‐temperature (UHT) metamorphism in continental crust has been widely documented, but the heat source responsible for generating these extreme conditions over a short period of time remains enigmatic. Here, garnet orthogneiss, spinel‐bearing granulite, and gabbronorite from the east Khondalite belt, China, have been analyzed via integrated geochemistry, U‐Pb zircon isotope geochronology, and phase equilibria modeling to shed light on the timing and nature of rapid UHT metamorphism in this area. Peak metamorphism is characterized in garnet orthogneiss by the assemblage garnet + orthopyroxene + plagioclase + K ‐ feldspar + quartz, which is calculated to represent pressure–temperature conditions of 0.83–0.88 GPa at 930–990 °C. Zircon ages from this sample yield an igneous (protolith) emplacement age of approximately 1.93–1.95 Ga, which matches the timing of metamorphism in adjacent (pre‐UHT) metapelites. These garnet orthogneiss were then metamorphosed to UHT conditions at approximately 1.92 Ga, coincident with emplacement of mantle‐derived gabbronorites, as supported by REE patterns in zircon, and evidence for a rapid thermal pulse in the east Khondalite belt lower crust at that time. Heat‐source and heat‐transfer calculations indicate that advected heat from mafic magmas is the most likely cause of this regional‐scale event, although ductile shearing might have contributed to a lesser degree. Key Points: Petrological modeling shows that garnet orthogneiss registered peak condition of 0.83–0.88 GPa at 930–990 °C High‐precision zircon dating result shows garnet orthogneiss experienced UHT metamorphism immediately after emplacement Heat flow calculations indicate advective heat from mafic magmas would be the heat source for rapid UHT metamorphism